What do memes tell us about the image of Arab modern women: A cyber pragmatics analysis of memes in a prominent Arabic Instagram account - Resty Syahrotul Aini; Delami; Awliya Rahmi; Arif Rahmatul Aji; Nurul Amin bin Mustafa (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
Diverse studies over the portrayal of women in memes have led to narratives and opposition against women, typically expressed by both feminists and anti-feminists. Despite numerous prior studies, the elaboration of Arabic memes remains significantly restricted. This study seeks to elucidate the image of contemporary Arab women as shown in memes. A qualitative descriptive study utilised memes from the prominent Arabic Instagram account @mzajeat.lady as the data source. Presupposition category analysis employing a cyberpragmatics approach was used to examine the representations of women within the pragmatic meanings of each meme. According to the presupposition types, contemporary Arab women are more physically and intellectually empowered, allowing them to break free from masculinity. Arab women may function without men due to psychological stability. Self-actualisation allows women to achieve their goals and pursue different activities. They are confident and can choose their marriages. The findings indicate a substantial transformation in the perception of contemporary Arab women. Meme, as conveyed on social media, represents liberation from the constraints of patriarchal culture that is often oppressive and confining. The findings significantly contribute to altering the preconceptions and stigmas historically associated with them. Furthermore, these findings advance the discourse of feminism on social media by introducing new and previously unexamined data on Arab memes.